The Role Of Online Media In Shaping The Popularity Of Political Parties In The 2024 Election In Indonesia - Asriadi Asriadi; Yusa’ Farchan; Wiyono (INJECT (Interdisciplinary Journal of Communication), 2025)
This study analyzes the popularity of political parties and official competitor in the 2024 political decision. This kind of examination is qualitative with a Qualitative Data Analysis Software (QDAS) approach. Research data were obtained from 90 factual, actual, sharp news documents focused on research themes sourced from online media detik, tribunnews, kompas, and pikiranrakyat in the past year. The projection analysis of this research data uses the NVivio 12 Plus device. The analysis results show that online media has high intensity towards the popularity of political parties and presidential candidates in the 2024 election. Four online media mention Nasdem Party, Democrat Party, KIB Party, PDI.P, and Gerindra Party more frequently. In addition, the names of the popular presidential candidates in the 2024 election in four online media are Anies Baswedan, Ganjar Pronowo, Prabowo Subianto, Airlangga Hartanto, and Muhaimin Iskandar. The implication is that online media will play a role with high intensity towards the popularity of political parties in Indonesia; even in the upcoming 2024 elections, online media will be seen to tend to one of the political parties and presidential candidates being carried out.